Liver abscesses in cattle: A review of incidence in Holsteins and of bacteriology and vaccine approaches to control in feedlot cattle - Amachawadi, R. G.; Nagaraja, Tiruvoor G. (My University, 2016)
Liver abscesses are the primary liver abnormality of feedlot cattle at slaughter. The incidence of liver abscesses is highly variable, but generally ranges from 10% to 20%. The incidence of total and the proportion of severely abscessed livers (A+) are greater in Holsteins fed for beef production and culled dairy cows than in beef breeds. The reason for the greater incidence of liver abscesses in Holstein steers is not known, but one of the reasons is likely because of increased days on feed. The high prevalence in cull cows is likely because no specific intervention, such as use of tylosin in the feed, is approved for use in dairy cows. Liver abscesses are generally a sequela to ruminal acidosis and rumenitis in cattle fed diets high in readily-fermentable carbohydrates and low in roughages; thus, the term "acidosis-rumenitis-liver abscess complex." Liver abscesses are almost always polymicrobial infections with Gram negative anaerobes constituting the predominant flora. Almost all studies have concluded that Fusobacterium necrophorum, a ruminal bacterium, is the primary causative agent and Trueperella (formerly Arcanobacterium) pyogenes is the secondary pathogen. A limited number of studies have been done on the bacterial flora of liver abscesses of culled dairy cows and Holstein feedlot steers. A recent study has reported on isolation of Salmonella from liver abscesses of Holstein cattle. The control of liver abscesses in feedlot cattle has depended on the use of antibiotics, particularly tylosin, in the feed combined with sound nutritional management to minimize occurrence of acidosis and subsequent rumenitis. Although there is no evidence of resistance development in F. necrophorum, the future of tylosin use as a feed additive in feedlot cattle is uncertain. Regardless, beginning January 2017, the use of tylosin in feedlot cattle for the prevention of liver abscesses will be under veterinary oversight. Although tylosin is widely used in the feedlot industry, there is considerable interest in evaluating antibiotic alternatives, such as essential oils and vaccines, to control liver abscesses. Because liver abscess is a bacterial infection and the pathogenicity and virulence factors of F. necrophorum have been studied widely, there have been considerable interest and efforts to develop an efficacious vaccine. The 2 antigens that have been targeted for vaccine production are leukotoxin and outer membrane proteins of F. necrophorum.
Citation: Amachawadi, R. G., & Nagaraja, T. G. (2016). Liver abscesses in cattle: A review of incidence in Holsteins and of bacteriology and vaccine approaches to control in feedlot cattle. Journal of Animal Science, 94(4), 1620-1632. doi:10.2527/jas2015-0261
Keywords: Bacteriology; Beef Breeds; Holsteins; Liver Abscesses; Tylosin; Vaccine